Single mode lasing from hybrid hemispherical microresonators - Chen, Rui (2013)
Enormous attention has been paid to optical microresonators which hold a great promise for microlasers as well as fundamental studies in cavity quantum electrodynamics. Here we demonstrate a three-dimensional (3D) hybrid microresonator combining self-assembled hemispherical structure with a planar reflector. By incorporating dye molecules into the hemisphere, optically pumped lasing phenomenon is observed at room temperature. We have studied the lasing behaviors with different cavity sizes, and particularly single longitudinal mode lasing from hemispheres with diameter ∼15 μm is achieved. Detailed characterizations indicate that the lasing modes shift under varying pump densities, which can be well-explained by frequency shift and mode hopping. This work provides a versatile approach for 3D confined microresonators and opens an opportunity to realize tunable single mode microlasers.